Formation of hollow silica nanospheres by reverse microemulsion. Issue 21 (8th May 2015) - Lin, Cheng-Han; Chang, Jen-Hsuan; Yeh, Yi-Qi; Wu, Si-Han; Liu, Yi-Hsin; Mou, Chung-Yuan
Abstract : Formation of hollow silica nanospheres in a water-in-oil microemulsion. Abstract : Uniform hollow silica nanospheres (HSNs) synthesized with reverse microemulsion have great application potential as nanoreactors because enzymes or nanocatalysts can be easily encapsulated de novo in synthesis. Water-in-oil (w/o) reverse microemulsions comprising the polymeric surfactant polyoxyethylene (5) isooctylphenyl ether (Igepal CA-520), ammonia and water in a continuous oil phase (alkanes) coalesce into size-tunable silica nanoparticles via diffusion aggregation after the introduction of silica precursors. Here, we elucidate in detail the growth mechanism for silica nanoparticles via nucleation of ammonium-catalyzed silica oligomers from tetraethylorthosilicate (TEOS) and nanoporous aminopropyltrimethoxy silane (APTS) in the reverse microemulsion system. The formation pathway was studied in situ with small-angle X-ray scattering (SAXS). We find a four-stage process showing a sigmoidal growth behavior in time with a crossover from the induction period, early nucleation stage, coalescence growth and a final slowing down of growth. Various characterizations (TEM, N2 isotherm, dynamic light scattering, zeta potential, NMR, elemental analysis) reveal the diameters, scattering length density (SLD), mesoporosity, surface potentials and chemical compositions of the HSNs. Oil phases of alkanes with different alkyl chains are systematically employed to tune the sizes of HSNs by varying oil molar volumes, co-solvent amounts or surfactant mixture ratios. Silica condensation is incomplete in the core region, with the silica source of TEOS and APTS leading to the hollow silica nanosphere after etching with warm water.